A novel truncated fusion gene ETV6::AC010198.2 in post-MPN acute myeloid leukemia caused by del(12)(p13p11) - Lu, Jiao; Yang, Guanqun; Zhang, Qiurong; Wang, Man; Wang, Lijun; Chen, Lu; Chen, Haoyue; Jiang, Xin; Liu, Chunhua; Lin, Tong; Han, Qiaoyan; Liu, Zefa; et al. (Frontiers in Oncology, 2025)
The gene ETV6 has been confirmed to be a genetic susceptibility gene for thrombocytopenia and leukemia. Here, we report a long-chain noncoding RNA AC010198.2 as a novel fusion partner of ETV6, showing a karyotype of del(12)(p13p11), with poor prognosis in a post-MPN AML that has never been reported, which may be an vital initial event in the transformation of MPN to AML and deterioration of disease.